Vital ethnographies: music and, youthful identities Hip Hop in Medellín: Hip hop en Medellín - Garcés Montoya, Ángela (Folios, revista de la Facultad de Comunicaciones y Filología, 2010)
This chapter is part of the research on “Musical Youthful Mediations”, the start point is the need of analyze the stereotypes that point out and, become weak to the young people in marginal and urban contexts, where is necessary to recognize at the Young people as producer of cultura related with the social and economic conditions which determine them. For this reason the main goal is to explore and identify the differents shapes of appropiation and reconfiguration of the identity made by the youthful cultures through of the musical arena, with its many ways: body, image, sound, musical composition, which showing the significances, senses and sensibilities that go around of the alternative-media.